Survei Teknik Dasar Passing Kaki Bagian dalam Peserta Ekstrakurikuler Futsal SMK Pamor Cikampek - Abdul Rohman; Bambang Ismaya; M. Mury Syafei (Peneliti.net, 2021)
Futsal extracurricular participants at SMK Pamor Cikampek, Cikampek District, Karawang Regency are still lacking in basic techniques of passing the inside foot of a futsal ball. This study aims to determine the level of basic inner leg passing techniques for futsal extracurricular participants at SMK Pamor Cikampek, Cikampek District, Karawang Regency. This research is a descriptive quantitative or quantitative descriptive research. The method used is a survey with data collection techniques through tests of basic foot passing techniques in the futsal ball game. The subjects in this study were futsal extracurricular participants at SMK Pamor Cikampek, namely in class X and class XI from TKR 1&2, TKJ, and OTKP with a total of 15 students. The data analysis technique used descriptive analysis as outlined in the form of a percentage. Based on the results of the study, it can be concluded that the basic technique survey of the inner foot passing of the futsal extracurricular participants at SMK Pamor Cikampek is in the